Lipid vesicles chaperone an encapsulated RNA aptamer - Ranajay Saha; Samuel Verbanic; Irene A. Chen (Nature Communications, 2018)
So far little is known about how encapsulation affects the activity and folding of RNA, which is of interest for understanding the origin of cellular life. Here the authors show that encapsulation of functional RNA in vesicles increases RNA activity and improves RNA folding through a biophysical confinement effect.